Place branding in rural areas: A literature review - Fuad Jafarli; Maurizio Canavari (AIMS Agriculture and Food)
The paper examines the concept of place branding in rural areas, highlighting its significance in increasing reputation, attracting investment, improving competitiveness, and fostering a sense of pride and belonging among local populations. This article provides a literature review of rural branding, examining the trends of the main topics, analyses, and methodological approaches used in investigating place branding. The analysis is based on 45 articles from the Scopus and Web of Science databases, organized into seven main topics: tourism, rural identity, rural and regional development, sustainability, food and gastronomy, stakeholders' involvement, and landscape. Additionally, the study integrates a conceptual framework that outlines the interplay between these themes, emphasizing the theoretical grounding of rural place branding. The findings indicate a positive trend in the number of articles published on rural place branding, a predominance of qualitative research methods, and a strong focus on theoretical framework analysis. The study also highlights the role of sustainability in rural place branding, demonstrating how the synergy of cultural heritage preservation, stakeholder collaboration, and landscape branding significantly enhances the local economy, fosters community pride, and promotes regional agri-food products and gastronomy. These elements contribute to the sustainable growth of rural regions while reinforcing their unique identity within competitive global markets.